Organic Broadband THz Generators Optimized for Efficient Near‐Infrared Optical Pumping. Issue 20 (3rd September 2020) - Shin, Myeong‐Hoon; Kim, Won Tae; Kim, Se‐In; Kim, Seung‐Jun; Yu, In Cheol; Kim, Sang‐Wook; Jazbinsek, Mojca; Yoon, Woojin; Yun, Hoseop; Rotermund, Fabian; Kwon, O‐Pil
Abstract: New organic THz generators are designed herein by molecular engineering of the refractive index, phonon mode, and spatial asymmetry. These benzothiazolium crystals simultaneously satisfy the crucial requirements for efficient THz wave generation, including having nonlinear optical chromophores with parallel alignment that provide large optical nonlinearity; good phase matching for enhancing the THz generation efficiency in the near‐infrared region; strong intermolecular interactions that provide restraining THz self‐absorption; high solubility that promotes good crystal growth ability; and a plate‐like crystal morphology with excellent optical quality. Consequently, the as‐grown benzothiazolium crystals exhibit excellent characteristics for THz wave generation, particularly at near‐infrared pump wavelengths around 1100 nm, which is very promising given the availability of femtosecond laser sources at this wavelength, where current conventional THz generators deliver relatively low optical‐to‐THz conversion efficiencies. Compared to a 1.0‐mm‐thick ZnTe crystal as an inorganic benchmark, the 0.28‐mm‐thick benzothiazolium crystal yields a 19 times higher peak‐to‐peak THz electric field with a broader spectral bandwidth (>6.5 THz) when pumped at 1140 nm. The present work provides a valuable approach toward realizing organic crystals that can be pumped by near‐infrared sources for efficient THz wave generation. Abstract : Organic crystals, which are designed through molecular engineering of the refractive index, phonon mode, and spatial asymmetry, simultaneously satisfy the crucial requirements for efficient and broadband THz wave generation, particularly at near‐infrared pump wavelengths near 1100 nm.